Secondary Cleft Rhinoplasty in 1720 Patients: Are National Practices Consistent With Guidelines?. (April 2020) - Chouairi, Fouad; Torabi, Sina J.; Gabrick, Kyle S.; Persing, John A.; Alperovich, Michael
Objective: To assess the timing, type, and associated adjunct procedures for secondary cleft rhinoplasty nationally. Design: Data were extracted from a national database of all secondary cleft rhinoplasty procedures (Current Procedural Terminology [CPT] codes 30460 and 30462). Frequency statistics were utilized to analyze demographics, comorbidities, surgical procedures, and timing. Chi-squared analysis and Fisher exact test were used for analysis. Setting: National Surgical Quality Improvement Program-Pediatric Database. Participants: A total of 1720 patients met inclusion criteria for secondary cleft rhinoplasty repair. Interventions: No relevant intervention. Main Outcomes and Measures: Age, demographics, comorbidities, and associated procedures. Results: Over 5 consecutive years, 1720 patients underwent secondary cleft lip rhinoplasty nationally. Mean patient age was 9.3 ± 5.3 years. Unilateral cleft rhinoplasty patients were older (9.0 years) than bilateral patients (7.8 years; P = .001). Rib grafting was performed in 6.3% of patients at a mean age of 10.6 years with a higher proportion of Asian and female patients. Auricular grafts were more commonly performed by otolaryngology than plastic surgery. The most common adjunct procedures included secondary cleft lip revision (33.1%) and tympanostomy tube placement (10.2%). When subdividing by type of cleft rhinoplasty, tip rhinoplasty was performed at a mean age of 7.3 years compared to rhinoplasty with osteotomies and a major septal component at 12.1 years ( P < .001). Conclusions: This study reveals that a large proportion of cleft rhinoplasties are performed in skeletally immature patients. Although patients undergoing rib grafting, nasal osteotomies, and a major septal component were older, these procedures are still performed in a large proportion of patients who are younger than expected.